Normal coronary arteriogram. An avoidable test?. Issue 6 (December 1982) - Ilsley, C; Stockley, A; Clitsakis, D; Layton, C
Abstract : Between 10 and 20% of coronary arteriograms in patients with chest pain show normal vessels, often in association with a history of "atypical" angina. Conventional non-invasive tests are inaccurate in this group of patients compared with those with classical angina. This study prospectively evaluates combined 12 lead exercise electrocardiography and thallium-201 scintigraphy as a screening test in patients with atypical angina in order to determine whether normal arteriograms are avoidable in this important subgroup of patients presenting with chest pain. Sixty seven consecutive patients with atypical angina underwent both maximal exercise testing and thallium scintigraphy before coronary arteriography. Chest pain during exercise was a poor predictor of coronary disease in this group. Eleven (16%) had abnormal arteriography, with the sensitivity of exercise and thallium tests being 45% and 73%, respectively. When both tests were applied the predictive accuracy for normal coronary arteries was 96% (54/56) and that for the presence of coronary disease was 82% (9/11). If coronary arteriography was withheld in patients in whom both the exercise test and thallium scintigraphy were negative, the number of normal coronary arteriograms could be reduced with only a very small risk of failing to detect individuals with coronary disease.